2016
DOI: 10.1051/shsconf/20162601073
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of life satisfaction in Canada: A causal modeling approach

Abstract: Abstract. Most research studies on Life Satisfaction/Subjective Wellbeing (SWB) have focused on one main determinant and a variety of social demographic variables to delineate the determinants of life satisfaction. However, very few research studies examine life satisfaction from a holistic approach. The aim of this study was to utilize a holistic approach to construct a causal model and identify major determinants of life satisfaction. This study utilized data from the General Social Survey, with a sample siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Lastly, we examined the interaction effect between annuitized income and mental/physical health on financial well-being. Past studies found evidence that physical and mental health conditions are directly related to individuals' financial well-being (e.g., Çelik et al 2017;Branch-Allen and Jayachandran 2016;Temple and Williams 2018). This study contributes to this body of literature by exploring whether annuitized income mediates the negative effect of poor mental/physical health on individuals' financial well-being.…”
Section: Introductionmentioning
confidence: 83%
“…Lastly, we examined the interaction effect between annuitized income and mental/physical health on financial well-being. Past studies found evidence that physical and mental health conditions are directly related to individuals' financial well-being (e.g., Çelik et al 2017;Branch-Allen and Jayachandran 2016;Temple and Williams 2018). This study contributes to this body of literature by exploring whether annuitized income mediates the negative effect of poor mental/physical health on individuals' financial well-being.…”
Section: Introductionmentioning
confidence: 83%
“…Although infectious disease, malnutrition, and mortality have been lowered in children and adolescent populations, however, shifting attention to chronic diseases, mental health problems, obesity, and physical illness, which their prominence during childhood and adolescence is very concerning (3). Life satisfaction (LS) and self-rated health (SRH), assess different dimensions of individuals' own health that show some non-biomedical factors of general well-being framed by individual, familial and social dimensions (4). LS can be de ned as the degree to which an individual judges the overall quality of his life-as-a-whole favorably (5).…”
Section: Introductionmentioning
confidence: 99%
“…Although infectious disease, malnutrition, and mortality have been lowered in children and adolescent populations, however, shifting attention to chronic diseases, mental health problems, obesity, and physical illness, which their prominence during childhood and adolescence is very concerning (3). Life satisfaction (LS) and self-rated health (SRH), assess different dimensions of individuals' own health that show some non-biomedical factors of general well-being framed by individual, familial and social dimensions (4). LS can be defined as the degree to which an individual judges the overall quality of his life-as-a-whole favorably (5).…”
Section: Introductionmentioning
confidence: 99%